The University of the Philippines College in Manila an institutional study - Kim, Isabel (Cunada)
The mission and objectives of the College at the different stages of its operation since its establishment in June 1951 to the First Semester 1973-74 has been consistent with university goals. The administration before the seventies failed to provide for continuing development and improvement of instructional staff who were largely part-time. However, since 1970-71 the College has employed young instructional staff and gradually made provisions for faculty development through promotions, research, seminars and further training. Originally, the clientele of the College was limited primarily to the working student but by SY 1960-61, more than 80 percent of the student enrolment were full-time students. The financial resources of the past have been inadequate and expenses were limited to the minimum essentials. Improved financial support in the seventies paved the way for improvements, developments and expansion of programs and services beyond the requirements of simple maintenance.